Macroeconomic effects of Federal Reserve forward guidance - Jeffrey R. Campbell; Charles L. Evans; Jonas D. M. Fisher; Alejandro Justiniano (Federal Reserve Bank of Chicago, 2012)
A large output gap accompanied by stable inflation close to its target calls for further monetary accommodation, but the zero lower bound on interest rates has robbed the Federal Open Market Committee (FOMC) of the usual tool for its provision. We examine how public statements of FOMC intentions - forward guidance - can substitute for lower rates at the zero bound. We distinguish between Odyssean forward guidance, which publicly commits the FOMC to a future action, and Delphic forward guidance, which merely forecasts macroeconomic performance and likely monetary policy actions. Others have shown how forward guidance that commits the central bank to keeping rates at zero for longer than conditions would otherwise warrant can provide monetary easing, if the public trusts it. We empirically characterize the responses of asset prices and private macroeconomic forecasts to FOMC forward guidance, both before and since the recent financial crisis. Our results show that the FOMC has extensive experience successfully telegraphing its intended adjustments to evolving conditions, so communication difficulties do not present an insurmountable barrier to Odyssean forward guidance. Using an estimated dynamic stochastic general equilibrium model, we investigate how pairing such guidance with bright-line rules for launching rate increases can mitigate risks to the Federal Reserve's price stability mandate.
Keywords: 330